The Cognitive Recovery Program for chronic schizophrenic patients - Wirakarat, Jularat (วารสารสุขภาพจิตแห่งประเทศไทย, 2013)
Objective Objective To develop and evaluate the effectiveness of Cognitive Recovery Program for chronic schizophrenic patients. Materials and methods The quasi-experiment, pre-post one group design was carried out in a chronic schizophrenic ward at Srithanya Psychiatric Hospital in May 2012. All 10 patients were recruited to the study. The Cognitive Recovery Program (CRP) was developed according to concepts of observation, organization and association. There were 20 2-hour-sessions covering 5 domains i.e. orientation, recall, attention, calculation and language. Mini Mental State Examination-Thai (MMSE), a quality of life scale (QOL) and activity daily life (ADL) scale were applied before and after the program. Wilcoxon signed rank test was analyzed means of 3 scales. Results All patients had MMSE score lower than normal before entering the program. After the program, all cases had increase MMSE score, and 4 cases had scores at normal level. Mean score of MMSE, QOL were significant higher than those before study except ADL. Conclusion The Cognitive Recovery Program could improve/maintenance cognitive function in schizophrenic cases. However, consistency of practice is essential otherwise cognitive function might be decline. In addition, diversity model for specific cognitive training program of the chronic schizophrenic patients who depend on the caregiver should be created.